Pengaruh ROA dan DER Dimoderasi oleh Kepemilikan Manajerial Terhadap Nilai Perusahaan - Yura Karlinda Wiasa Putri; I Made Endra Lesmana Putra (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Firm value is an important concept for investors because it is a market measure of the firm's overall value. In this study, the purpose of this study is to examine the impact of ROA and DER on firm value, with management ownership as a moderating variable. Firm value is the dependent variable which is measured using Tobin's Q. In this study, the analytical technique used is moderated regression analysis. The test results, the first ROA has a large and good impact on the value of the consumption sector company, while the second managerial ownership cannot moderate the impact of ROA on the company value, the third DER has a large and good impact on the consumption sector company value. and fourth, managerial ownership strengthens the effect of DER on firm value. The limitation of this study lies in the classification of the sample which only uses the consumption sector for the period 2018 – 2020 as a result, the results of the study cannot be generalized to see the effect of the variables used on manufacturing companies as a whole.